Needs Analysis and Programme Planning in Adult Education - Sava, Simona (Study guides in Adult Education, 2012)
How to identify, analyse, and assess the various types of adult learning needs? How to develop programmes tailored to these needs? This study guide is written for postgraduate students preparing to become professional adult educators, as well as for those intending to plan educational programmes for adults. The book covers the various types of adult (learning)needs and provides hints on how to identify, analyse, and assess these needs. It presents typical challenges involved in performing such an analysis as well as theoretical considerations of the concept and types of needs, of diagnosing educational needs and their theoretical understanding. The author draws conclusions on how to develop programmes tailored to the needs identified. With a focus on practical concerns, she illustrates the necessary steps as well as the factors to be considered when designing an educational programme for adults, both in the planning stage and in the stages of implementation and evaluation. From the Contents: The Importance of Needs Analysis and Programme Planning in Adult Education Needs: Theoretical Considerations Fields of Needs Analysis in an Educational Context Methods of Needs Analysis in Adult Education Needs Analysis for Planning Educational Programmes Steps in Programme Planning in Adult Education